A cell-free enzymatic activity assay for the evaluation of HIV-1 drug resistance to protease inhibitors - Matsunaga, Satoko; Masaoka, Takashi; Sawasaki, Tatsuya; Morishita, Ryo; Iwatani, Yasumasa; Tatsumi, Masashi; Endo, Yaeta; Yamamoto, Naoki; Sugiura, Wataru; Ryo, Akihide (Frontiers in Microbiology, 2015)
Due to their high frequency of genomic mutations, human retroviruses often develop resistance to antiretroviral drugs. The emergence of drug-resistant human immunodeficiency virus type 1 (HIV-1) is a significant obstacle to the effective long-term treatment of HIV infection. The development of a rapid and versatile drug-susceptibility assay would enable acquisition of phenotypic information and facilitate determination of the appropriate choice of antiretroviral agents. In this study, we developed a novel in vitro method, termed the Cell-Free Drug Susceptibility Assay (CFDSA), for monitoring phenotypic information regarding the drug resistance of HIV-1 protease (PR). The CFDSA utilizes a wheat germ cell-free protein production system to synthesize enzymatically active HIV-1 PRs directly from PCR products amplified from HIV-1 molecular clones or clinical isolates in a rapid one-step procedure. Enzymatic activity of PRs can be readily measured by AlphaScreen (Amplified Luminescent Proximity Homogeneous Assay Screen) in the presence or absence of clinically used protease inhibitors (PIs). CFDSA measurement of drug resistance was based on the fold resistance to the half-maximal inhibitory concentration (IC50) of various protease inhibitors (PIs). The CFDSA could serve as a non-infectious, rapid, accessible, and reliable alternative to infectious cell-based phenotypic assays for evaluation of PI-resistant HIV-1.